Williamsdale - Central Mapping Authority of New South Wales (Bathurst, N.S.W : C.M.A., 1983)
Property maps of New South Wales showing land ownership.
Diazo print.
Index to adjoining sheets.
Keywords: Real property -- New South Wales -- Williamsdale -- Maps; Land tenure -- New South Wales -- Williamsdale -- Maps; Williamsdale (A.C.T.) -- Maps; Cadastral maps